PLANNING TO REPAIR THE APPROACH SLABS BRIDGE MUARA TABIRAI, RANTAU – KANDANGAN - Ade Nafis Prawira (Universitas Lambung Mangkurat, 2021)
Muara Tabirai Bridge is on the border between Rantau and Kandangan District ,which is precisely is on the street of Kalumpang-Margasari, the village of Paci, Kalumpang subdistrict. Increasing economic growth has led to the economy of the population being affected by the development of the city, gradually increasing in economic sectors as a result of global economic growth. The increase in this economy is due to the growing industry in the area. This is accompanied by the increase and needs of the population in the area that resides in the region. Unfortunately, after one year of construction of Muara Tabirai Bridge, the approach slabs bridge in the direction Kandangan on the right side suffered a decrease in the soil to damage the asphalt, due to the possibility of a landslide on the side of the road, then the implementers make alternative repairs by using a bronjong which makes the load heavier than before so that the ground that supports the burden of the heap, bronjong and traffic load can not withstand and So in this final task is done repair on the ground soil and design a retaining wall that is more suitable for the condition of the landThe basic soil repair method used is by a phased heap (Preloading) combined with the Prefabricated Vertical Drain (PVD) ,which serves as a water and air release on the soil, thus experiencing a consolidated degree of 90%. And for retaining wall against the side of the heap is used sheet pile with the type of free-standing ,which is suitable for the location of the pile located in the river. After that, the calculation of budget plan (RAB) on the Land, improvement Project,From the result of calculation obtained, a gradual heap (Preloading) carried out 0.2 m/week ,and ,a high critical heap (HCR) obtained on the high end of the plan (HR) 3.14 m obtained a security figure (SF) of 1.148 so that the heap used the soil reinforcement that is Mini pile erection so that the safety number (SF) reaches more than equal to 1.5 Prefabricated Vertical Drain (PVD) is used specification of the product PT. Teknindo Superior System installed when before done the filling is on the ground ground, planning Prefabricated Vertical Drain (PVD) using a triangular mounting pattern with a distance between PVD 1.25 m, depth 28 m and the time required is 21 weeks. Planning of soil retaining structure used is cantilever sheet pile type, obtained a total length of sheet pile of 20.938 m at STA 0 + 275 on the left and right side of the bridge. The budget plan for this basic land improvement project is Rp. 30,886,527,167